Epidemiological characteristics of fall injuries and their related outcome in Riyadh, Saudi Arabia: A descriptive study from a Level-I trauma center - Suliman Alghnam; Alaa S Alsayyari; Jawaher A Towhari; Rawabi M Alsayer; Maha Y Almohaimeed; Mohammed H Aldebasi; Ibrahim T Albabtin (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Falls are the leading cause of admissions for trauma emergency in Saudi Arabia. However, the scarcity of evidence of what the burden of falls is locally limits the understanding of the underlying risk factors and hinders planning of effective prevention. The objective of this study was to describe patients' characteristics and health outcomes after hospital admissions as a result of a fall injury. MATERIALS AND METHODS: A retrospective analysis was conducted using a trauma registry from a level-I trauma center in Riyadh. All patients admitted as a result of a fall between 2001 and 2018 were included (n = 4825). Variables included were demographics, mechanism of fall, length of hospital stay, surgery, intensive care unit admission, intubation rate, and severity of the injury. For continuous variables, means and standard deviations were calculated, whereas, frequencies and proportions were used to describe categorical variables. Chi-squared tests were used to compare variables across age groups, and F test was used to compare the means of continuous variables. RESULTS: Majority of the patients (63.6%) were male and about 39% of the sample were children. The most common mechanism of falls was standing (52.6%) followed by slipping (23.0%). Overall, limb fractures were the most common injury (73.3%). While upper limb fractures were more common in children (44.5%; P < 0.01), lower limb fractures were more prevalent among the older patients (70.2%; P < 0.01). Fall injuries in the elderly were significantly associated with higher mortality (3.5%; P < 0.01). CONCLUSION: This study highlights the significant burden fall injuries impose on population health. Prevention programs may use these findings to guide and tailor interventions for specific age groups. Furthermore, this study underlines the need for a national recording system for injuries to guide policymakers in evidence-based decisions.